Neurologic aspects of systemic disease. - Biller, Jose; Ferro, Jose M. (Handbook of clinical neurology, 2014)
Neurologic Aspects of Systemic Disease is a comprehensive reference focusing on brain and central nervous system impacts related to systemic disease. Part I covers cardiovascular disease, pulmonary diseases, renal diseases and rheumatologic/musculoskeletal disease.